A church based approach in cooperative organizing a case study of the Calvario Multi-Purpose Cooperative in Janiuay, Iloilo - Decafe-Nicolasora, Mary Jun (2000)
Development can only be achieved when all sectors are considered essential to the success of the various efforts geared towards this goal. Thus, cooperative organizing is a must. However, the success or failure of this activity greatly depends on the values acquired by the organizer and on the principles and philosophies that him or her in his or her endeavor. Even up to this point in time, only a few of the cooperative organized survived and this few include those organized by church-based organization. Whereas, the most popular among the cooperatives that failed where those that were government-initiated like the FACOMA and the Samahang nayon. Therefore, it can be concluded that something is wrong with the govenrment's approach in cooperative organizing leading to these failures. This study however, did not deal with this issue but was bent on answering the following qquestions: 1. What is the bearing of a church-based approach in the success or failure of the cooperative oragnizing? and 2. Does the memebrs and networks aencies' pereption on the status of their cooperative have a bearing on its successful operation? Three chruch-based cooperative boast of exemplary performance in cooperative operation. What is common though to all of them is the emphasis put on human touch or social relations. Similarly, the Janiuay Calvario Multi-Purpose Cooperative (JCMPC) envisioned a Christ-Centered Cooperative through sharing and fellowship. Furthermore, the members emphasized that smooth-interpersonal-relations among the leaders, amangement staff and the members indicate the cooperative's success. The management staff on the other hand, said that they serve well the cooperative because of the weekly devotional and self-reflection activity facilitated for them. This is why they believed taht the Calvario Evangelical Church has really an impact on the success of their cooperative. moreover, the CDA and the CARE-Philippines representatives believed the same because, according to them, there is a unity in purpose and mindset of the management staff and the key leaders due to homogeneity. However, the members cannot identify with this opinion because nothig is done to bring them into a Christ-centered consciousness. Therefore, the JCMPC has still a long way to go to bring into fruition their vision of a Christ-centered community. They still have to learn from the strategies employed by the other cooperative such as the Sta. Catalina Multi-Purpose Cooperative in North Cotabato. This cooperative gave due attention to the basic Christian education of its member to ensure solidarity and institutionalization. The success of a cooperative cannot just be measured in the increase of the member's number and the amount they have, but it should be measured along with the values, cooperativism has bring forth to the members. Likewise, the member's' perception on the status of their cooperative also served to strengthen tha validity of the identified success indicators.
Research Paper (Cooperative Management). -- Iloilo City : UPV-[CM], June 2000.